Exploring Effective Training Methods to Improve Football Performance: Effects of Small Sided Games on Cardiovascular Endurance - Abd Karim, Zulakbal; Arif Hanis Abd Ghani, Muhammad; Md Nadzalan, Ali (International Journal of Engineering and Technology, 2018)
This study is aimed to examine the effects of small-sided game training on the cardiovascular endurance among football players. A total of 30 university football players were involved in this study. Participants involved in six weeks of small sided games training and Yo-Yo intermittent recovery level 1 test was conducted pre- and post-training intervention. Descriptive statistics, paired and independent t-test were conducted in data analysis. The results showed that there was a significant difference between the training group and the control group in cardiovascular endurance levels at post-intervention test. In conclusion, a small sided game training is a valuable training method to be implemented in enhancing physical abilities among football players.Â